Seeing inequality? Relative affluence and elite perceptions in Mexico - Alice Krozer (United Nations Research Institute for Social Development (UNRISD), 2020)
Among the many approaches attempting to explain the persistence of inequalities, the role of perceptions and relative measures remains under-explored. Based on over 40 in-depth interviews with members of the Mexican elite, this paper examines how the dissonance between elite perceptions and measured economic status matters for the social construction and perpetuation of inequality. This unique empirical data reveals that the "wealth bubbles" within which elites exist lead to an experience of relative affluence: although elites acknowledge being privileged compared to a majority of the population, they simultaneously feel poorer compared to the exceptionally wealthy peers in their social space. Consequently, despite showing concern about inequality and its negative effects, elites underestimate their own position in the overall income distribution, re-centring the distribution around their own incomes. Understanding elites as embedded in their particular sociality helps explain how the accumulation of advantages assures persistently high inequality in the country. For instance, where elites feel they "earned" their own social position through personal merit, they might insist on education as the key to overcoming inequality, even though due to the stratified opportunity structures in the country, such a "remedy" will actually perpetuate inequality, as it centralizes privileges rather than equalizing opportunities. Meanwhile, elites' distorted perceptions of the majority's wellbeing affects social cohesion by further alienating them from the rest and obstructs the implementation of effective policy to sustainably decrease inequality. Hence, elites' policy recommendations, based on their perceptions, perpetuate inequality, meaning that ultimately perceptions end up influencing inequality levels.
Keywords: 330; Inequality; elites; income distribution; perceptions; Mexico